Hypofractionated helical intensity-modulated radiotherapy of the prostate bed after prostatectomy with or without the pelvic lymph nodes - the PRIAMOS trial - Krause, Sonja; Sterzing, Florian; Neuhof, Dirk; Edler, Lutz; Debus, Jürgen; Herfarth, Klaus (BMC cancer, 2012)
While evidence on safety and efficacy of primary hypofractionated radiotherapy in prostate cancer is accumulating, data on postoperative hypofractionated treatment of the prostate bed and of the pelvic lymph nodes is still scarce. This phase II trial was initiated to investigate safety and feasibility of hypofractionated treatment of the prostate bed alone or with the pelvic lymph nodes.